Transsaccadic Scene Memory Revisited: A 'Theory of Visual Attention (TVA)' Based Approach to Recognition Memory and Confidence for Objects in Naturalistic Scenes. - Melissa L.-H. Võ; Werner X. Schneider; Ellen Matthias (Bern Open Publishing, 2008)
The study presented here introduces a new approach to the investigation of transsaccadic memory for objects in naturalistic scenes. Participants were tested with a whole-report task from which - based on the theory of visual attention (TVA) - processing efficiency parameters were derived, namely visual short-term memory storage capacity and visual processing speed. By combining these processing efficiency parameters with transsaccadic memory data from a previous study, we were able to take a closer look at the contribution of visual short-term memory capacity and processing speed to the establishment of visual long-term memory representations during scene viewing. Results indicate that especially the VSTM storage capacity plays a major role in the generation of transsaccadic visual representations of naturalistic scenes.